"When a woman is pregnant, her grave is open": health beliefs concerning dietary practices among pregnant Kalenjin women in rural Uasin Gishu County, Kenya - Roselyter Monchari Riang'a; Anne Kisaka Nangulu; Jacqueline E.W. Broerse (BMC, 2017)
Abstract Background Reducing malnutrition remains a major global challenge especially in low- and middle-income countries. Lack of knowledge on the motive of nutritional behaviour could ultimately cripple nutrition intervention outcomes. The purpose of this study was to investigate how health beliefs influence nutritional behaviour intention of the pregnant Kalenjin women of rural Uasin Gishu County in Kenya. The study findings provide useful information for culturally congruent nutrition counselling and intervention. Methods In this qualitative study semi-structured interviews were conducted with 42 pregnant and post-natal (with children less than one year) Kalenjin women in selected rural public health facilities of Uasin Gishu County Kenya. Furthermore, key informant interviews took place with 6 traditional birth attendants who were also pregnancy herbalists, two community health workers and one nursing officer in charge of Maternal and Child Health (MCH) for triangulation and provision of in-depth information. Content analysis of interview transcripts followed a grounded theory (Protection Motivation Theory) approach, using software MAXQDA version 12.1.3. Results Abstracted labour (big babies and lack of maternal strength), haemorrhage (low blood), or having other diseases and complications (evil or bad food) were the major perceived health threats that influence nutritional behaviour intention of the pregnant Kalenjin women in rural Uasin Gishu County in Kenya. Conclusion The pregnancy nutritional behaviour and practices of the Kalenjin women in rural Uasin Gishu County act as an adaptive response to the perceived health threats, which seem to be within the agency of pregnant women. As a result, just giving antenatal nutritional counselling without addressing these key health assumptions that underlie a successful pregnancy outcome is unlikely to lead to changes in nutritional behaviour.